ADOPTION AND STRUCTURAL RACISM: THE INVISIBILITY OF BLACK CHILDREN IN THE FOSTER CARE SYSTEM AND THE NEED FOR AFFIRMATIVE ACTION POLICIES (Editora Impacto Científico, 2026)
The article addresses the impacts of structural racism in the context of adoption of Black children and adolescents in Brazil. The general objective is to investigate and demonstrate the intrinsic relationship between the selectivity in profile choices in the adoption process and the perpetuation of structural racism. The specific objectives are: to analyze the phenomenon of structural racism and its relationship with the adoption of Black children and adolescents in Brazil; and to analyze the invisibility of Black children and adolescents in the National Adoption System (SNA) through the lens of Structural Racism, demonstrating how the selectivity in the profiles desired by applicants, combined with institutional biases, compromises the effectiveness of the right to family coexistence for this portion of the child and youth population. The research problem seeks to investigate the following question: In what way does structural racism manifest itself in the selectivity of the desired profile by adoption applicants, impacting the realization of the right to family coexistence for Black children and adolescents in Brazil? The methodology employed in the study is based on a qualitative and exploratory research approach, utilizing bibliographical research techniques.  DOI: https://doi.org/10.56238/edimpacto2025.090-094